UV/O3 assisted InP/Al2O3–Al2O3/Si low temperature die to wafer bonding - Anantha, P. (2015)
Direct bonding of InP dies to Si wafer at low temperature utilizing Al2O3 high-κ dielectric as the interfacial material for homogeneous bonding is reported. The bonding technique is assisted with a UV/Ozone exposure for surface activation and the activation time is optimized for the various intermediate layer thicknesses (5, 10, 20 nm). After the pre-bonding stage, annealing is carried out at 300 °C for 3 h. A bonding interface with minimal interfacial voids is reported for low intermediate layer thickness. The bonding interfaces are examined and a homogeneously bonded interface is shown in the IR images as well as in the FIB micrographs. Additionally a heat transfer simulation is also carried out and the InP/Al2O3–Al2O3/Si bonded structure is shown to closely match the thermal characteristics of a direct bonding approach with no intermediate layer. A high quality bonding interface is revealed along with improved heat dissipation characteristic for Al2O3 interface. Therefore, Al2O3 proves to be an advantageous candidate for its use in potential Si photonic integrated circuits application.